INTEGRATION OF LISTENING STRATEGY INSTRUCTION IN ADVANCING SCHOOL LEARNERS’ OUTCOMES - Oserbay Feruza; Karbozova Gulnara Kumisbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In communication, an important place is given to the perception of information by ear, which is, listening. The ability to perceive and understand foreign speech by ear is one of the most important skills in mastering a foreign language. In the theory of foreign language teaching methodology, the concept of listening was introduced by researcher E.I. Passov. According to his research, listening is the understanding of speech in a foreign language by ear. In his writings, he suggests distinguishing between the two concepts of listening and listening.